2008
DOI: 10.1104/pp.107.115188
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Transcriptional Changes in Response toClavibacter michiganensissubsp.michiganensisReveal a Role for Ethylene in Disease Development  

Abstract: Clavibacter michiganensis subsp. michiganensis (Cmm) is a gram-positive actinomycete, causing bacterial wilt and canker disease in tomato (Solanum lycopersicum). Host responses to gram-positive bacteria and molecular mechanisms associated with the development of disease symptoms caused by Cmm in tomato are largely unexplored. To investigate plant responses activated during this compatible interaction, we used microarray analysis to monitor changes in host gene expression during disease development. This analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 74 publications
9
106
3
2
Order By: Relevance
“…Interestingly, gene expression was down-regulated after inoculation with bacterial pathogens Ralstonia solanacearum and Erwinia chrysanthemi (Berrocal-Lobo et al 2002). A similar observation was documented from our previous study where the tomato SN2 gene was down-regulated less than twofold upon Cmm infection (Balaji et al 2008). Down-regulation of defense genes by some pathogens has been suggested as a mechanism to overcome plant defense (Jakobek et al 1993).…”
Section: Introductionsupporting
confidence: 53%
“…Interestingly, gene expression was down-regulated after inoculation with bacterial pathogens Ralstonia solanacearum and Erwinia chrysanthemi (Berrocal-Lobo et al 2002). A similar observation was documented from our previous study where the tomato SN2 gene was down-regulated less than twofold upon Cmm infection (Balaji et al 2008). Down-regulation of defense genes by some pathogens has been suggested as a mechanism to overcome plant defense (Jakobek et al 1993).…”
Section: Introductionsupporting
confidence: 53%
“…tomato is correlated with the intercellular level of salicylic acid (Carviel et al, 2009). Transcriptional analysis of young tomato plants in response to Cmm infection revealed that a subset of host genes is highly induced, including defence-related genes, production and scavenging of free oxygen radicals and hormone synthesis (Balaji et al, 2008). It might be hypothesized that in older tomato plants, enhanced host defence responses lead to an increased ARR response to Cmm.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR reactions were performed with FAST SYBR master mix, 23 (ABI, http://www.appliedbiosystems.com) in a 25 mL volume using an Applied Biosystems StepOnePlus real-time PCR system (ABI) with the following cycling program: 10 min at 95°C, 15 s at 95°C followed by 40 cycles of 1 min at 60°C, 15 s at 95°C, and 1 min at 60°C. The comparative DDCT method was performed according to Balaji et al (2008).…”
Section: Quantitative Reverse Transcription Pcr Analysismentioning
confidence: 99%